Ultrasonic velocities in carbonates: laboratory data versus a new squirt-flow dispersion model - De Paula, Osni; Gurevich, Boris; Pervukhina, M.; Makarynska, Dina (EAGE, 2009)
One of the main targets of oil exploration companies nowadays are carbonate reservoirs because of the huge amounts of oil discovered in carbonates recently. Prediction of petrophysical properties of carbonates is a challenge due to the diversity of these reservoir rocks. In order to investigate main petrophysical trends such as velocity-porosity or velocity-permeability in carbonate rocks, the ultrasonic measurements are undertaken in many laboratories worldwide. However, use of Gassmann’s relations to incorporate fluid saturation effects and predict velocities of saturated rock at seismic frequencies is problematic. As was shown in a number of works which reported both increase and decrease of elastic moduli with saturation, Gassmann’s relations do not work well on carbonates samples. The softening of elastic moduli is assumed to be caused by chemical transformation of carbonates and/or frame dissolution with saturation. The stiffening of carbonate rock with saturation is shown to be caused by the local flow (squirt) between pores of different shapes and orientations and expected to be captured with Mavko and Jizba high frequency relations.In this study we analyze the experimental ultrasonic measurements in dry and saturated carbonates where pore geometry is assumed to be mostly responsible for the departure from the Gassmann’s relation. However, the measured moduli do not match the predictions of Mavko and Jizba (1991) relations either. This indicates that the measurement frequency is not high enough to inhibit pressure communication between compliant and stiff pores. Here we use a new squirt model recently developed by Gurevich et al. (2009b) in order to derive the moduli of saturated carbonates from “dry” moduli and to predict aspect ratios of compliant pores and attenuation of P- and S-waves.